Gambaran Burnout Pada Komunitas Pelari Rekreasional - Rifqi Rahmat Albari; Umi Anugerah Izzati (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to describe the phenomenon of burnout among the recreational running community in Surabaya. The research employs a descriptive qualitative approach involving six participants, consisting of a community leader, two coaches, and three community members. Data were collected through in-depth interviews and participatory observation. The findings indicate that burnout manifests in three main forms that reflect the general dimensions of burnout: emotional exhaustion, withdrawal from community activities, and a decreased sense of personal accomplishment. These three aspects are interrelated and affect runners’ motivation, training consistency, and social involvement within the community. In conclusion, burnout among recreational runners is a complex psychological phenomenon influenced by activity demands, social pressure, and individuals’ perceptions of their own performance. Keywords: Burnout, Emotional Exhaustion, Sports Community, Recreational Runners’ Motivation